Pengaruh Sales Growth, Inventory dan Operating Capacity Terhadap Cash Holding - Prasetiyo, Budi; Fitria, Yunita (Jurnal Akuntansi dan Governance Andalas, 2021)
This study aims to determine the effect of sales growth, inventory, and operating capacity on cash holding in mining companies listed on the Indonesia Stock Exchange. The sample was determined based on the purposive sampling method of 31 companies during 2015-2019. The data source used is in the form of financial reports for 2015-2019 and 2014 financial reports are needed to help calculate the sales growth variable so that 155 data are obtained. Data is obtained from Indonesian Stoke Exchange (IDX). Data analysis techniques used Multiple Linear Regression. The results of this study indicated that the sales growth and inventory variables had a negative and insignificant effect on cash holding and operating capacity had a significant positive effect on cash holding